Assessment of beneficial role of an insectivorous bird, jungle babbler (Turdoides striatus) predation, on Helicoverpa armigera infesting pigeon pea (Cajanus cajan) crop - Bhavna Bharucha; G. S. Padate (Acta Agronómica)
Jungle babbler (Turdoides striatus), a widely spread sub-tropical insectivorous passerine is considered beneficial to agro-ecosystem, as they devour voraciously on insect matter especially Helicoverpa armigera, the gram pod borer, a notorious pest infesting and causing heavy loses to crops like pigeon pea (Cajanus cajan) which is a vital crop of semi-arid tropical and subtropical farming system, providing high quality vegetable protein. Helicoverpa is known to feed on flowers, pods, and seeds and is the most important biotic constraint affecting pigeon pea yields. Jungle babblers have a peculiar foraging style which helps expose the Helicoverpa larvae as well as pupae through various phenological stages of pigeon pea. For comparative assessment of their beneficial role and as a possible bio control agent, in Baroda city (State of Gaujarat), India, was studied, two crops of pigeon pea (insecticide treated and untreated (control) were selected. In both treated and control crops, the number of jungle babblers were maximum in pigeon pea fields during october and november in both small pod stage and large pod stage which had heavy infestation of Helicoverpa. Least number of birds was seen during the flowering stage in September. Later in treatment crop three applications of Dunnate and Monocrotophos insecticide spray was done after which the pest population decreased which is reflected in number of birds in the field, while the bird number in control crops grew since insecticide spray was not done and number of larvae increased with the stage of the crop. Along with the main crop pigeon pea, comparative study was also done to see the food preference by these birds in crops like sorghum, maize, cow pea and ploughed and unploughed fields. Maximum number of birds was seen in unploughed field and least in sorghum suggesting that Helicoverpa is preferred food over sorghum grains thus pigeon pea and sorghum can be used as mixed crops to protect the crop from heavy losses. This work investigates the interactions among pigeon pea, its key pest, and their natural enemies. These relationships have implications on the pest status of individual species and on possible control strategies.